The DELTA® nursing measure: Its development and testing for nursing utility - Hendrik J. Loubser; Judith C. Bruce; Daleen Casteleijn (AOSIS, 2013)
In the specialised nursing field of acute mental illness nurses expressed a need to measure and evaluate their patients' mental-health outcomes both empirically and routinely. The aim was to develop and test a measurement tool, named the DELTA nursing measure, which could be embedded routinely into the nursing process and care plans, enabling the psychiatric nurses to score and evaluate their patients' acute mental-health outcomes. A qualitative, exploratory study design was used to address two sequential objectives. Firstly, qualitative data that described observable behaviours in patients with acute mental illness were collected from psychiatric nurses (n = 5) who were experienced in acute mental healthcare. The data were analysed using inductive content analysis techniques to design and construct the DELTA nursing measure. In the second objective, the nursing utility of the DELTA nursing measure was studied. This was done by training and testing a new team of psychiatric nurses (n = 25) working in a 116-bed acute psychiatric hospital, in the application of the DELTA nursing measure. After 30 months a focus group (n = 6) representing this team was held to explore their perceptions and experiences of the nursing utility of the newly-developed measure. The descriptive data were analysed using deductive content analysis techniques. The outcome of the DELTA nursing measure as a routine nursing measure of acute mental illness provided good results. The nursing-utility characteristics have confirmed positive responses with regard to its acceptance, usefulness and confidence as a worthwhile tool to be used in expediting nursing services in acute mental healthcare. The positive responses to the DELTA nursing measure are noteworthy. It has the potential to add substantial value to the mental health care field in nursing by adding a measurable dimension to patient outcomes, a much needed requirement by patients, multidisciplinary teams and healthcare funders. In die gespesialiseerde verplegingsveld van akute psigiatrie het verpleegkundiges 'n behoefte uitgespreek om roetineweg pasiënte se geestesgesondheidsuitkomste empiries te meet en te evalueer. Die doel van die studie was om 'n meetinstrument, genoemd die 'DELTA nursing measure', te ontwikkel en toets wat ingebed kan word in die verplegingsproses en versorgingsplan en wat psigiatriese verpleegkundiges in staat kan stel om roetine-weg die pasiënte se akute geestesgesondheidsuitkomste te meet en te evalueer. 'n Kwalitatiewe, eksploratiewe studie ontwerp is gebruik om twee opeenvolgende doelwitte aan te spreek. Eerstens is kwalitatiewe data wat observeerbare gedrag in pasiënte met akute geestessiektes beskryf ingesamel van psigiatriese verpleegkundiges (n = 5) wat ervaring het in akute geestesgesondheidsorg. Die data is geanaliseer met induktiewe inhouds analiese tegnieke om die ontwerp en konstruksie van die 'DELTA nursing measure' te bewerkstellig. In die tweede doelwit was die 'DELTA nursing measure' se bruikbaarheid vir verpleging bestudeer. Om dit te doen was 'n nuwe span psigiatriese verpleegkundiges (n = 25) wat werksaam was in 'n 116-bed akute psigiatriese hospitaal opgelei en getoets in die gebruik van die 'DELTA nursing measure'. Na 30 maande is 'n fokusgroep (n = 6) gehou wat verteenwoordigend was van die span om hulle persepsies en ervarings van die nuut-ontwikkelde meetskaal se bruikbaarheid te eksploreer. Beskrywende data is met behulp van deduktiewe inhouds tegnieke geanaliseer. Die uitkoms van die 'DELTA nursing measure' as 'n routine verplegingmeetskaal vir die bepaling van akuutheid in psigiatrie het baie goeie resultate opgelewer. Die bruikbaarheidseienskappe het positiewe response bevestig dat aanvaarding, betroubaarheid en vertroue bereik is en dat dit 'n nuttige instrument is om die verplegingsdiens te bevorder. Die positiewe response op die 'DELTA nursing measure' is merkwaardig. Dit het die potensiaal om 'n betekenisvolle bydrae te lewer tot die psigiatriese verplegingsveld omdat dit 'n meetbare dimensie toevoeg tot pasient uitkomste, 'n hoogs-benodigde vereiste van pasiënte, multidissiplinêre spanne en gesondheidsorgbefondsers.